A method for evaluating the wind disturbance rejection capability of a hybrid UAV in the quadrotor mode. (August 2019) - Zhang, Hang; Song, Bifeng; Wang, Haifeng; Xuan, Jianlin
The wind disturbance rejection capability of a quadrotor fixed-wing hybrid unmanned aerial vehicle (QFHUAV) in the quadrotor mode is an important factor restricting its large-scale applications. In this paper, based on static equilibrium analysis of the quadrotor mode of a QFHUAV with a wind disturbance, a method for analyzing and evaluating the wind disturbance rejection capability of the QFHUAV in the quadrotor mode is presented. The six degrees-of-freedom (6-DOF) static equilibrium equations of the QFHUAV are established in headwind and crosswind situations. The maximum wind velocity that satisfies the equilibrium equations under the constraints of the maximum thrust and torque of the quadrotor propulsion system is used to determine the wind disturbance rejection capability of the QFHUAV in the quadrotor mode. A QFHUAV with a twin-boom is used as an example to analyze and evaluate its wind disturbance rejection capability in the quadrotor mode. The configuration parameters, quadrotor propulsion system parameters, and aerodynamic parameters affecting the wind disturbance rejection capability of the QFHUAV in the quadrotor mode are presented, discussed, and explained. The yawing moment from the wind disturbance is the main factor threatening the safe flight of the QFHUAV in the quadrotor mode. The rotor disk angle, the maximum thrust of the quadrotor propulsion system, and the moment arms of the components of the quadrotor propulsion system thrust are the main factors affecting the wind disturbance rejection capability of the QFHUAV in the quadrotor mode. Increasing these parameter values is an effective approach to improve the wind disturbance rejection capability of the QFHUAV in the quadrotor mode. From the perspective of wind disturbance rejection capability, tailless and X-type layouts are better choices for QFHUAVs. The correctness of results obtained by the proposed method is verified by two flight test schemes.